Examining Linkage Factors in Stock Prices - Ajeng, Putri; Suun, Muhammad; Subhan, Subhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the influence of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS) on the stock prices of companies included in the LQ45 index and listed on the Indonesia Stock Exchange during the 2019-2021 period. The research hypothesizes that each of these financial metrics has a significant impact on stock prices. Research Design and Methodology: The research adopts a quantitative approach, utilizing secondary data from company financial reports on the Indonesia Stock Exchange website. The sample, comprising ten issuers, was selected using purposive sampling. The analysis was conducted using the Statistical Product and Service Solutions (SPSS 26) software to assess the relationships between the independent variables (ROA, ROE, NPM, EPS) and the dependent variable (stock prices). Findings and Discussion: The findings reveal that ROA and NPM positively and significantly impact stock prices, indicating that companies with higher returns on assets and profit margins are likely to experience increases in their stock prices. Conversely, ROE has a negative and significant effect on stock prices, suggesting that higher returns on equity may not always align with higher stock prices. Additionally, EPS has a positive and significant effect on stock prices, highlighting its importance as a profitability measure for investors. Implications: These results have practical implications for investors and company management, suggesting that improving ROA, NPM, and EPS can positively influence stock prices. However, the negative relationship between ROE and stock prices warrants further investigation. Future research should explore the underlying reasons for this inverse relationship and consider additional variables that may impact stock price movements.